Gender and ethnic differences in incidence and survival of lymphoid neoplasm subtypes in an Asian population: Secular trends of a population‐based cancer registry from 1998 to 2012. Issue 11 (25th June 2015) - Lim, Raymond Boon Tar; Loy, En Yun; Lim, Gek Hsiang; Zheng, Huili; Chow, Khuan Yew; Lim, Soon Thye
Abstract : Descriptive epidemiology on incidence and survival by lymphoid neoplasm (LN) subtypes using the 2008 World Health Organisation (WHO) classification remained limited in Asia. The aim of this study was to evaluate whether gender and ethnic differences in incidence and survival of LN subtypes existed using the Singapore Cancer Registry (SCR) from 1998 to 2012. We derived age standardised incidence rates (ASIRs) by the direct standardisation method and 5‐year relative survival (RSR) by the Ederer II method and period approach. Five‐year observed survival (OS) was obtained for each ethnicity. Malays had the highest ASIR of total LNs among the three ethnicities for each time period. The largest increase in 5‐year RSR subtypes was follicular lymphoma from 43.8% in 1998–2002 to 82.3% in 2008–2012; followed by chronic lymphocytic leukaemia (CLL)/small lymphocytic lymphoma (SLL) from 48.1% in 1998–2002 to 77.9% in 2008–2012. Although males had higher incidence than females in each time period, females had greater 5‐year RSR for follicular lymphoma (89.8% in 2008–2012 for females vs . 76.6% in 2008–2012 for males) and CLL/SLL (78.7% in 2008–2012 for females vs . 76.7% in 2008–2012 for males). All three ethnicities experienced an overall increase in 5‐year OS for mature B‐cell lymphoma, with Indians experiencing the greatest increase (37.1% in 1998–2002 to 61.1% in 2008–2012), followed by Malays (30.8% in 1998–2002 to 48.7% in 2008–2012) and then Chinese (36.4% in 1998–2002 to 51.3% in 2008–2012). Our study demonstrated that improved mature B‐cell lymphoma survival was not only observed in the West, but also in Singapore. Abstract : What's new? How does gender and ethnicity affect cancer survival? These researchers looked at incidence and survival statistics for lymphoid cancer in Singapore and compared the rates among Chinese, Malay, and Indian ethnic groups. They found the highest incidence rate among Malays, for all lymphoid neoplasms, and males of all three groups had higher incidence rates than females, and lower survival rates. Comparing data from 1998 to 2002 and 2008 to 2012, they found that all three ethnicities showed improved 5‐year survival rates for mature B‐cell lymphoma, with the biggest gains occurring among Indians.